Experimental dynamic stall study of an airfoil in turbulent flow - Marañón Di Leo, Julio (2017)
The objective of this study is to experimentally determine the fluid dynamic configuration of the dynamic stall of an airfoil in turbulent flow. Wind tunnel tests were carried out in order to characterize the airfoils behavior in static and static after a quick change in the angle of attack (“dynamic case”) using flow visualization, loads and hot-wire anemometry measurements at different Reynolds numbers and with one rate of change for the angle of attack. In all the tests, a Worthmann FX 63-137 airfoil model was used. First, with the visualizations made using a paint technique, for the different configurations, some differences in the flow pattern were found and points of interest in the airfoil were chosen. In those points, the sensors for the velocity measurements were placed. With the velocities acquired using a hot-wire system, autocorrelations, turbulence intensities, density power spectrums and wavelet maps were calculated and compared between the static and the dynamic case; different results were found and explained. Additionally, differences were traced in the turbulent intensities in the wake of the airfoil. Furthermore, a wavelets analysis was performed, and the flow scales obtained show differences for the same conditions analyzed before.